Substrate-perforated and compact ultra-wideband antenna with WLAN band rejection - Shareef, Wessam Zayd; Ismail, Alyani; Alhawari, Adam Reda Hasan (Cambridge University Press and the European Microwave Association, 2015)
This paper presents a designed notched band ultra-wideband (UWB) printed antenna using coplanar waveguide-fed configuration. Simple technique of perforating the substrate and modifying the ground plane and radiator patch was used to achieve UWB for the designed antenna at smaller structure. Narrow arch-shaped slot was introduced to the patch of the proposed antenna to obtain the band rejection function around the 5.4 GHz frequency to avoid the interference with WLAN applications. The proposed antenna was fabricated and the measurement result is found in well agreement with the simulation result. In addition to the acquirable UWB bandwidth, the designed antenna is capable to exhibit high radiation efficiency and omni-directional pattern.